Pendampingan Kemitraan Program Teknologi Tepat Guna Dengan Badan Usaha Milik Desa - Ibrahim Ibrahim; Nurhayati Nurhayati; Yeni Sulastri; Mursal Ghazali (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this community service is to assist with appropriate technology program partnerships with village-owned enterprises in Lepak Village, East Lombok. The implementation of assistance is carried out by carrying out several activities including: 1) coordination with the coconut oil business manager 2) Coordination with the BUMDes Party and 3) bringing together the coconut oil manager with the BUMDes Party and the Lepak Village Head, East Lombok. Activities to obtain results include: 1) BUMDes is ready to cooperate in providing the raw materials needed and serving marketing; and 2) the village will coordinate with related parties to assist future business development in the form of business capital breakthroughs. This activity provides opportunities for the community to develop the Appropriate Technology program business that is being pioneered